1993
DOI: 10.3109/10826089309039664
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Registered Nurses toward Alcoholic Patients in a General Hospital Population

Abstract: The Marcus Alcoholism Questionnaire was administered to 66 registered nurses at a community hospital to ascertain their attitudes regarding alcoholic patients in a general hospital population. This was done to provide documentation on what nurses attitudes actually are as opposed to making an assumption about what they should be because of the high visibility of the problem of alcoholism. The author reports the results of the study and then contrasts them with information about registered nurses attitudes towa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
2
18

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 4 publications
3
27
2
18
Order By: Relevance
“…In this study, none of the participants reported receiving drug and alcohol training (Crothers & Dorrian, 2011). In contrast, in a study in a small community hospital with a specialised inpatient drug and alcohol program, nurses reported positive attitudes to working with drinkers (Allen, 1993). Indeed, similar to studies in doctors, nursing studies have consistently indicated gaps and opportunities for training in the identification, treatment and ongoing support of patients with alcohol-related issues (Anderson, Eadie, MacKintosh, & Haw, 2001;Owens, Gilmore, & Pirmohamed, 2000).…”
Section: Interactions With Healthcare Professionalsmentioning
confidence: 76%
See 1 more Smart Citation
“…In this study, none of the participants reported receiving drug and alcohol training (Crothers & Dorrian, 2011). In contrast, in a study in a small community hospital with a specialised inpatient drug and alcohol program, nurses reported positive attitudes to working with drinkers (Allen, 1993). Indeed, similar to studies in doctors, nursing studies have consistently indicated gaps and opportunities for training in the identification, treatment and ongoing support of patients with alcohol-related issues (Anderson, Eadie, MacKintosh, & Haw, 2001;Owens, Gilmore, & Pirmohamed, 2000).…”
Section: Interactions With Healthcare Professionalsmentioning
confidence: 76%
“…Studies yield expressions of interest from nursing staff in working more in this area, and requests for more training (Anderson et al, 2001;Owens et al, 2000). This is clearly an important area for development, since education results in more positive attitudes to care (Allen, 1993;Geirsson et al, 2005).…”
Section: Interactions With Healthcare Professionalsmentioning
confidence: 99%
“…Fato que não se observa na literatura internacional em que os estudos datam de mais de três décadas (8) . Estudo (10) objetivando identificar as atitudes de enfermeiras de um hospital norte americano, evidenciou que as mesmas acreditavam que: fatores emocionais são importantes causas do alcoolismo; o alcoolista é incapaz de controlar sua ingestão alcoólica; bebedores sociais podem ser alcoolistas, e que o álcool é capaz de causar dependência. Esses mesmos enfermeiros estavam ainda menos dispostos a crer que: o alcoolista não quer se recuperar e que são pessoas fracas.…”
unclassified
“…Esses estudos evidenciaram, que o estereótipo atribuído ao alcoolismo e ao alcoolista influencia diretamente nas atitudes dos profissionais enfermeiros (Wallston, Wallston, De Velli, 1976;Cornish, Miller, 1976) (Gross, Lismam, 1979 (Allen, 1993), pela primeira vez, os fatores apontados pelos enfermeiros, como causas importantes do controle do uso de álcool pelos usuários foram o aumento do conhecimento e a mudança de atitudes positivas nos profissionais (Hegemaster et al, 1993;Gerace, Hughes, Spunt, 1995) para trabalhar com pacientes não alcoolistas (Grief, Elliott, 1994) e a discriminização do usuário de álcool (Krueger, 1995).…”
Section: Atitudes De Enfermeiros Frente Ao áLcool Alcoolismo E Alcoounclassified